2008
DOI: 10.1007/978-3-540-89982-2_55
|View full text |Cite
|
Sign up to set email alerts
|

Safe Formulas in the General Theory of Stable Models (Preliminary Report)

Abstract: Abstract. Safe first-order formulas generalize the concept of a safe rule, which plays an important role in the design of answer set solvers. We show that any safe sentence is equivalent, in a certain sense, to the result of its grounding-to the variable-free sentence obtained from it by replacing all quantifiers with multiple conjunctions and disjunctions. It follows that a safe sentence and the result of its grounding have the same stable models, and that stable models of a safe sentence can be characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 7 publications
0
31
0
1
Order By: Relevance
“…By expanding the language to include new predicates, this logic can be embedded in classical first-order logic, [19], and this permits an alternative but equivalent formulation of the concept of stable model for first-order formulas, expressed in terms of classical, second-order logic [6]. The latter definition of answer set has been further studied in [10,11] where the basis of a first-oder programming language, RASPL-1, is described. An alternative approach to a first-order ASP language is developed in [8,7].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…By expanding the language to include new predicates, this logic can be embedded in classical first-order logic, [19], and this permits an alternative but equivalent formulation of the concept of stable model for first-order formulas, expressed in terms of classical, second-order logic [6]. The latter definition of answer set has been further studied in [10,11] where the basis of a first-oder programming language, RASPL-1, is described. An alternative approach to a first-order ASP language is developed in [8,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, NFN programs can be compiled into the standard DLV system. A second example is the definition of safety introduced by Lee, Lifschitz and Palla in [11] (we will call it here LLP-safety) defined essentially for arbitrary first-order formulas in such a way that the stable model of such a formula can be obtained by considering its ground version. It is also shown that the stable models of safe formulas form a (first-order) definable class.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations